Peran Mahasiswa KKN dalam Mengembangkan Program Keagamaan untuk Remaja di Masjid Desa Talang Empat - Panca Oktoberi; Mallfi Lutfia; Nisa Eftiana; Hafiz Zatul Alam; Wahyuni Sri Rezeki; Yarsi Putri; Ira Rama Dianti; Muhammad Farhan Kurniawan Neri; Oktaviona Anggraini; Gerry Ferdiand; Hanif Tuflihun Ngaban; Andika Saputra; Fuja Yauno Fitri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This study describes the role of community service (KKN) students in developing religious programs for teenagers at the mosque in Talang Empat Village, Bengkulu. The research responds to the low participation of youth in mosque activities due to irrelevant programs and a lack of engaging atmosphere. KKN students acted as change agents by initiating contextual and participatory programs such as Friday evening sermons, mosque cleaning, Qur'an recitation classes, Ramadan Islamic competitions, and the commemoration of Nuzulul Qur’an. A qualitative descriptive approach was used, with data collected through observation, interviews, and documentation. The results show a significant increase in youth involvement each week, especially in sermon and Qur’an learning activities. Students not only served as organizers but also as mentors and facilitators who built positive relationships and encouraged active participation. The program successfully revitalized the mosque's role as a center for youth religious development. This model of mosque-based community engagement proves to be an effective strategy for strengthening Islamic values among rural youth and is recommended for wider implementation.